Buildings of postal, telegraph and telephone services in Leiden 1850-1920 (Bulletin KNOB, 2007)
In Leiden the Post Office had already been accommodated in a building on Breestraat since the 18th century. When in 1859 the telegraph service was established in Leiden, the service was successively accommodated in various existing premises. In 1889 the service was housed in the premises to the right of the Post Office.Through an exchange with the parcel post department in 1895 the telegraph service obtained a fixed location on Bloemmarkt for the subsequent twenty years. The introduction of the public telephone service in the Netherlands in 1881 was the result of private initiative.Leiden acquired its first local telephone exchange in 1890. It was first accommodated in the attic of the town hall, later in the attic of the weigh house on Aalmarkt and finally, in 1905, on the upper floor of a dwelling on Papengracht. Long-distance telephone services started in 1888 by connecting the local telephone networks of one and the same private company.Already in 1897 the government decided to take over the entire existing - still very modest - long-distance telephone network in one go. Thus 'the public telephone service' came into being. In Leiden this new service was accommodated in the telegraph building on Bloemmarkt. In 1913 the government had started to take over the local private telephone networks.In 1919 it was the turn of Leiden. For this purpose the existing telegraph building on Bloemmarkt had to be fundamentally refurbished. This was done in the years 1918-1923. In that latter year the local telephone exchange on Papengracht was discontinued and transferred to Bloemmarkt.After the large refurbishments in the years 1918-1923 the complex of buildings of the PTT on Breestraat and Bloemmarkt, later renamed Boommarkt, remained unchanged in set-up for fifty years. It remained in use until 1972 and was demolished in January 1976.